(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In the 21st century, when information on pedagogic science is rapidly updated in the world, it is an important task to improve the knowledge on the Karakalpak folklore, skills and spiritual and moral qualities of pupils studying in the schools of the Republic of Karakalpakstan with the help of the pedagogical system. At the present time, the technologies of teaching Karakalpak folk language in senior classes of general secondary schools are of the pedagogical problems that have not been specially studied. This article considers the problem of the formation of innovative competence of future teachers based on digital technologies. The content of the concept of "innovative competence of the future teacher" is specified as a component of professional competence, which ensures the innovative level and quality of the educational process, the embodiment of the actual and potential abilities of its subjects.